Pre-performance physiological state: Heart rate variability as a predictor of shooting performance - Ortega, E.; Wang, C. J. K. (Applied Psychophysiology and Biofeedback, 2018)
Heart rate variability (HRV) is commonly used in sport science for monitoring the physiology of athletes but not as an indicator of physiological state from a psychological perspective. Since HRV is established to be an indicator of emotional responding, it could be an objective means of quantifying an athlete's subjective physiological state before competition. A total of 61 sport shooters participated in this study, of which 21 were novice shooters, 19 were intermediate shooters, and 21 were advanced level shooters. HRV, self-efficacy, and use of mental skills were assessed before they completed a standard shooting performance task of 40 shots, as in a competition qualifying round. The results showed that HRV was significantly positively correlated with self-efficacy and performance and was a significant predictor of shooting performance. In addition, advanced shooters were found to have significantly lower average heart rate before shooting and used more self-talk, relaxation, imagery, and automaticity compared to novice and intermediate shooters. HRV was found to be useful in identifying the physiological state of an athlete before competing, and as such, coaches and athletes can adopt practical strategies to improve the pre-performance physiological state as a means to optimize performance.